Bordetella hinzii Genomic Characteristics and Vaccine Target Discovery - Jin Rui; Mao Junjie; Deng Yuhang; Wu Wenwei; Liang Xuechen; Zheng Enhui; Li Quwen (Zoonoses)
This study was aimed at analyzing the pathogenic characteristics of Bordetella hinzii ( B. hinzii ), and elucidating its antibiotic resistance mechanisms, virulence gene distribution, and vaccine development potential. Genomes of 38 global strains were downloaded from the NCBI database. After quality control with CheckM, pan-genome analysis was performed with Roary, SNP-based phylogenetic trees were constructed with snippy, and antibiotic resistance genes (CARD database) and virulence genes (VFDB database) were predicted with abricate. Bioinformatics tools were integrated to screen candidate vaccine proteins. All strains carried intrinsic resistance genes, including efflux pumps ( MexAB-OprM ) and the β-lactamase HBL-1 , which conferred resistance to ten antibiotic classes. Core virulence genes ( bplA-L , bvgAS , and flagella-associated genes) were highly conserved (detection rate >92.1%). SNP analysis classified the strains into six clades, and human-derived isolates showed host-specific clustering. The pan-genome was open (7,530 genes; Heaps’ law parameter B = 0.35). Two outer membrane proteins, LptD and BamD, were identified as vaccine candidates (antigenicity scores >0.4; no host homology). B. hinzii exhibits cross-host transmission risks, driven by conserved virulence genes and an open genome enabling adaptive evolution. LptD and BamD represent potential vaccine targets requiring further validation. This study provides a theoretical basis for clinical management and prevention strategies.